2020
DOI: 10.7717/peerj.8455
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome sequences of three Merulinidae corals and novel insights into the phylogenetics

Abstract: Over the past few decades, modern coral taxonomy, combining morphology and molecular sequence data, has resolved many long-standing questions about scleractinian corals. In this study, we sequenced the complete mitochondrial genomes of three Merulinidae corals (Dipsastraea rotumana, Favites pentagona, and Hydnophora exesa) for the first time using next-generation sequencing. The obtained mitogenome sequences ranged from 16,466 bp (D. rotumana) to 18,006 bp (F. pentagona) in length, and included 13 unique prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The purifying selection of cold-water corals indicated that the deep-sea environment variation might be insufficient to induce alterations in genetic functionality. In addition, the atp8 gene, which plays an important role in ATP synthesis, exhibited the highest median K a/ K s value in selected cold-water coral species, consistent with previous studies in other organisms ( Kumar et al, 2020 ; Lv et al, 2018 ; Niu et al, 2020 ). Based on their higher K a/ K s ratios and increased amino acid changes, the atp8 and mutS genes may have evolved more rapidly, experiencing more relaxed selective constraints and accumulating more mutations.…”
Section: Discussionsupporting
confidence: 90%
“…The purifying selection of cold-water corals indicated that the deep-sea environment variation might be insufficient to induce alterations in genetic functionality. In addition, the atp8 gene, which plays an important role in ATP synthesis, exhibited the highest median K a/ K s value in selected cold-water coral species, consistent with previous studies in other organisms ( Kumar et al, 2020 ; Lv et al, 2018 ; Niu et al, 2020 ). Based on their higher K a/ K s ratios and increased amino acid changes, the atp8 and mutS genes may have evolved more rapidly, experiencing more relaxed selective constraints and accumulating more mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Identifying the driving force that shaped the GC content and deciphering the biological meaning of variations in the GC content will help us understand genome evolution [ 25 ]. The mitogenome GC content of most scleractinians ranged from 30% to 40% [ 22 , 26 , 27 , 28 ]. The intergenic regions of different genes ranged from −1 to 1506 bp.…”
Section: Resultsmentioning
confidence: 99%
“…PCR reaction mixture was totally 25 μL, including template DNA 1 μL, primers (forward and reverse) 2 μL, dNTPs 2 μL, Taq DNA polymerase 0.15 μL, buffer solution 2.5 μL, and sterile deionized water. The Eppendorf thermal cycler was used for PCR amplification following the standard procedures performed in Niu et al (2020) . The amplified products were purified and bidirectional sequenced in Personal Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial genomes of Anthozoa are atypical with a few distinguishing characteristics. It is manifested in the presence of conventional two tRNAs; All protein-coding genes (PCGs) stop the protein biosynthesis process with complete termination codons ( Fukami and Knowlton, 2005 , Niu et al, 2020 ); A DNA mismatch repair mechanism benefiting from the slow mutation rates ( Shearer et al, 2002 ); The relatively loose gene packing, featured by a series of noncoding regions ( Kitahara et al, 2014 ); And group I introns interrupting functional genes ( Beagley et al, 1998 , Emblem et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%